Students' perceptions on the use of selected mobile apps in the process of acquiring L2 pronunciation – a preliminary study - Matysiak, Aleksandra (Językoznawstwo, 2023)
The accessibility and multimodality of modern technologies make them particularly beneficial for pronunciation learning and teaching. Google Play Store offers more than 300 English pronunciation apps, many of which have received high ratings ranging from 4.5 to 4.9 out of 5 stars. Most of these apps are available for free. Due to their capacity for individualized, customized, self-paced “anytime – anywhere” learning and automated feedback on individual performance and progress, these apps are gaining increasing popularity among English learners worldwide. This paper reports on a small-scale study that examined five of the highest-rated free apps: Elsa Speak – Learning English Pronunciation by ELSA, English Pronunciation 2019 – Correct Pronunciation by Grounders, English Pronunciation by NVG Std, Pronounce It by Maclo Studios, and Quick Pronunciation Tool by Tiago English Tutor. Twenty first-year BA students of English Philology from the University of Łódź participated in the study by testing the five apps and answering questions related to their overall design, utility, potential for learning, teaching, and pronunciation assessment. The results of the study revealed the learners’ practical uses of the apps and their views on the value of using these apps for practising, teaching, and assessing English pronunciation skills.